Padrões epidemiológicos, sociodemográficos, clínicos e operacionais da sobreposição de caso de hanseníase em redes de convívio domiciliar em municípios das regiões Norte e Nordeste do Brasil - Boigny, Reagan Nzundu (2018)
Leprosy is part of the group of chronic and neglected infectious diseases with high detection of new cases (NC) in endemic areas in Brazil, especially in the North, Northeast and Central-West regions. The expression of more than 1 case of leprosy (overlapping) in families or home-contact networks (HCN) reflects greater vulnerability and increased risk. The objective of this study was to analyze epidemiological, sociodemographic, clinical and operational patterns of HCNs with overlapping of leprosy cases in municipalities of the states of Bahia, Piauí, and Rondônia, detected in the period from 2001 to 2014. It is a cross-sectional study with descriptive and analytical approaches. The study was organized in two stages. In the 1st, reference cases (RC) that had ≥1 person affected by leprosy in the same HCN were addressed. This stage was consolidated in Article 1: analysis of the occurrence of HCNs with overlapping of cases and their sociodemographic, economic and clinical profiles. In the 2nd stage, RC and their co-prevalent cases (CPC) in HCN with overlapping were addressed. This phase was composed by the Articles 2, 3 and 4. Of the total of 1032 cases included, 538 (52.1%) had >1 case in their HCN. In the group with overlapping cases stood out, cases of females sex (292, 54.3%), age between 41-60 years (240, 44.6%), elementary school (272, 50.6%), income <1 minimum wage, (265, 49.3%), and residence with ≥5 people (265, 49.3%), dimorph clinical form (341; 37.2%), multibacillary operational classification (506; 54.2%), and absence of leprosy reaction (327; 60.8%). Municipalities in the state of Rondônia presented greater overlap of cases in HCN (PR 1.23, 95% CI 1.07–1.43, p-value=0.003), as well as residing with ≥5 people (PR 1.27, 95% CI, 1.02–1.57, p-value=0.017), and had leprosy reaction (PR 1.15, 95% CI 1.02–1.29, p-value=0.018). In the 2nd stage, there was a new approach to 233 NLC of HCN with overlapping of the disease, among which 52.8% (n=123) were RC and the others, CPC. The majority belonged to HCN with ≥3 cases. There was a greater probability of having ≥3 cases in HCN when the case had residency in Bahia state (PR 1.24, 95% CI 0.99–1,55, p-value=0.047) and in rural areas (PR 1.58, 95% CI 1.17–2.13, p-value=0.006), no garbage collected by the city hall (PR 1.41, 95% CI 1.19–1.66, p-value=0.004), and inclusion in the Bolsa Família Program (PR 1.26, 95% CI 1.05–1.53, p-value=0.041). In 53.2% (n=124) the disease reached 2 generations, and in 20.2% (n=47), 3 generations. As to the degree of relationship between CR and PCC, the highest proportion was inbreeding (n=120, 51.3%). There was an association between the occurrence of leprosy in ≥2 generations and: living in municipalities in Bahia (PR 1.36, 95% CI 1.10–1.67, p-value <0.001), living in rural areas (PR 1,21, 95% CI 1.03–1.41, p-value=0.047), did not have a water distribution network (RP 1.26, 95% CI 1.08–1.47, p-value=0.042), and not have garbage collected (PR 1.29, 95% CI 1.12–1.48, p-value=0.018). The repetition of leprosy cases in the same HCN was a common event in the scenarios studied. It should be considered as an epidemiological marker of increased risk, with the potential to qualify health surveillance actions in the territories of primary care.